Pengaruh YouTube terhadap Perubahan Kemampuan Menulis Cerpen Siswa SMP di Tengah Dominasi Media Sosial - Aris Arisandi; Amir Hamzah; Heni Adhianata (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2026)
This study aims to determine the influence of using YouTube social media on the short story writing skills of students at SMPS Al-Miftah 4 Ketapang, Sampang, during the 2024/2025 academic year. The study is motivated by students' low interest and limited skills in writing short stories, resulting from conventional instruction that lacked variety. A quantitative approach utilizing the correlational method was employed. The study population comprised all students in grades I through III (106 students), with a sample of 51 students selected using Slovin's formula. Data collection techniques included questionnaires, interviews, observation, and documentation. Data analysis was conducted using the Product Moment correlation test. The results show a calculated r-value of 0.61, which exceeds the r-table value at significance levels of 5% and 1%. This demonstrates a reasonably strong correlation between YouTube usage and students' short story writing skills. Thus, YouTube, as an audiovisual learning medium, is effective in enhancing students' creativity, generation of ideas, and skills in writing short stories.